Epigenetics: possible applications in climate-smart crop breeding. (11th April 2020) - Varotto, Serena; Tani, Eleni; Abraham, Eleni; Krugman, Tamar; Kapazoglou, Aliki; Melzer, Rainer; Radanović, Aleksandra; Miladinović, Dragana
Abstract: To better adapt transiently or lastingly to stimuli from the surrounding environment, the chromatin states in plant cells vary to allow the cells to fine-tune their transcriptional profiles. Modifications of chromatin states involve a wide range of post-transcriptional histone modifications, histone variants, DNA methylation, and activity of non-coding RNAs, which can epigenetically determine specific transcriptional outputs. Recent advances in the area of '-omics' of major crops have facilitated identification of epigenetic marks and their effect on plant response to environmental stresses. As most epigenetic mechanisms are known from studies in model plants, we summarize in this review recent epigenetic studies that may be important for improvement of crop adaptation and resilience to environmental changes, ultimately leading to the generation of stable climate-smart crops. This has paved the way for exploitation of epigenetic variation in crop breeding. Abstract : Intense breeding has narrowed crop genetic diversity. Epigenetic diversity could emerge as new source of phenotypic variations to improve crop adaptation to a changing environment and generate stable climate-smart crops.